Alaska reunion : a Wild River novel - Snow, Jennifer (Snow, Jennifer. Wild River, 2021)
Still single, still working at the same bookstore and still pining for the guy who got away, Ellie Mitchell cringes at the prospect of attending her high school reunion. She just can't face showing up alone--with her dreams of becoming a teacher still unfulfilled--when her ex will be bringing a model-gorgeous plus-one. Callum McKendrick has been in love with Ellie since forever, but he's not sure his coworker takes him seriously. Offering to be her date for the reunion is his chance to show Ellie just what she's missing by being stuck in the past, but will becoming her fake boyfriend be enough to prove that Callum is her perfect match?